The Impact Of Green Finance On Market Value And Reputation Of Financial Service Companies - Endah Dewi Purnamasari; Shafiera Lazuarni; Nova Yanti Maleha (Universitas Indo Global Mandiri, 2024)
This study aims to analyze the impact of green finance implementation, including green bonds and green loans, on the market value and reputation of financial service companies in Indonesia. The research employs a quantitative approach with an explanatory research design. Secondary data, including financial reports, sustainability reports, and ESG scores, were obtained from financial service companies listed on the Indonesia Stock Exchange (IDX) during the 2015–2025 period. The sample consists of 70 companies selected using purposive sampling. The regression analysis results indicate that green bonds and green loans have a positive and significant impact on both market value and company reputation. Green loans show a greater effect compared to green bonds on both dependent variables, reflecting their flexibility and more direct influence on corporate sustainability. The model demonstrates that green finance accounts for 65% of the variation in market value and 70% of the variation in company reputation.This study confirms that green finance not only supports global sustainability goals but also offers significant benefits to financial service companies by enhancing their competitiveness and market image. Policy implications and strategies to promote the adoption of green finance in Indonesia are also discussed. Keywords: Green Finance,Market Value, Reputation